1985
DOI: 10.1128/aac.27.5.701
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial action of colistin (polymyxin E) against Mycobacterium aurum

Abstract: Mycobacterium aurum was susceptible to the antibiotic colistin (polymyxin E), which had an MIC of 5 ,ug/ml and an apparent bactericidal effect at concentrations above 50 ,ug/ml. Treatment of actively growing cells with sublethal concentrations of colistin (15 ,Ig/ml) resulted in synchronized cell division once the antibiotic was removed. Under conditions of synchronized cell growth, one cycle of DNA replication lasted 120 min and one cycle of cell division lasted about 180 min. Although the antibiotic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, there exist historical reports of polymyxins killing bacteria without actively lysing those cells (8,21). Here, we demonstrated that treatment with polymyxins induces hydroxyl radical production through the Fenton reaction and that this radical production mediates the rapid killing of A. baumannii, as well as E. coli and F. novicida.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, there exist historical reports of polymyxins killing bacteria without actively lysing those cells (8,21). Here, we demonstrated that treatment with polymyxins induces hydroxyl radical production through the Fenton reaction and that this radical production mediates the rapid killing of A. baumannii, as well as E. coli and F. novicida.…”
Section: Discussionmentioning
confidence: 75%
“…It has often been assumed that these membrane disruptions cause bacterial cell death directly through membrane lysis. However, reports from as far back as the late 1970s indicate that under certain conditions, polymyxins are capable of killing bacteria without lysis, suggesting that another mechanism of bacterial cell death may also be induced by treatment with these antibiotics (8,21).…”
mentioning
confidence: 99%
“…Disruption of the hydrophobic barrier can allow for an influx of INH, leading to enhanced bactericidal activity. Another possibly is that during the self-promoted uptake, INH has an enhanced uptake from the environment by the cells, once again leading to an influx within the cell and enhanced bactericidal killing [18]. The Fenton reaction [46] should be investigated an additional mechanism of action against MTB.…”
Section: Resultsmentioning
confidence: 99%
“…The authors [51] observed no enhancement of drug activity for CST with RIF or INH, but no antagonism was observed either. colistin interacts with the outer polysaccharide layer, causing it to be patchy, more election dense with a budding appearance [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation